Decoding and designing: Promising routes to tailor-made herbs - Jianwu Shi; Yu Wu; Lei Zhang (Science of Traditional Chinese Medicine, 2025)
Abstract. The ideal characteristics of herbs can be summarized as a high content of secondary metabolites, high stress resistance, desirable shape, and high yield. In this study, 2 strategies are proposed for decoding the biogenesis and quality formation mechanisms of active ingredients and targets for genetic breeding of yield and resistance in traditional Chinese medicine. First, multiomics can be applied in decoding the synthesis pathways of secondary metabolites and the mechanisms underlying the formation of desirable traits. Second, the identification of molecular markers and target genes associated with desirable traits in ideal herbs can be achieved through Genome-Wide Association Studies. Ideal herbs are further designed through genomic selection and gene editing technologies. These strategies will provide references for the investigation of herb breeding.